2020
DOI: 10.1186/s12889-020-08707-4
|View full text |Cite
|
Sign up to set email alerts
|

A rapid assessment of the implementation of integrated disease surveillance and response system in Northeast Nigeria, 2017

Abstract: Background Integrated disease surveillance and response (IDSR) is the strategy adopted for public health surveillance in Nigeria. IDSR has been operational in Nigeria since 2001 but the functionality varies from state to state. The outbreaks of cerebrospinal meningitis and cholera in 2017 indicated weakness in the functionality of the system. A rapid assessment of the IDSR was conducted in three northeastern states to identify and address gaps to strengthen the system. Method The survey was conducted at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…Improvements in IDSR system attributes such as completeness and timeliness of data reporting have been observed in Uganda, Malawi and Ghana [ 24 , 35 , 49 , 51 ]. By the end of 2017, 68% of the countries in the WHO Africa Region had achieved the timeliness and completeness threshold of at least 80% of the reporting facilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in IDSR system attributes such as completeness and timeliness of data reporting have been observed in Uganda, Malawi and Ghana [ 24 , 35 , 49 , 51 ]. By the end of 2017, 68% of the countries in the WHO Africa Region had achieved the timeliness and completeness threshold of at least 80% of the reporting facilities.…”
Section: Resultsmentioning
confidence: 99%
“…IDSR strategy strives for the concurrent integration route, but most countries have not achieved total integration. Implementation of the strategy is partially done [ 14 , 35 ], and there is more focus on technical aspects than organisational and human resource issues hence impair the performance of the systems [ 49 , 82 ]. Nevertheless, some countries such as Uganda have rectified those systemic challenges and reported improvement in the implementation [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…IDSR strategy strives for the convergent integration route but the majority of countries programmes have never achieved total integration. Implementation of the strategy is partially done [23,48] and there is more focus on technical aspects than organizational and workforce issues hence impairs the performance of the systems [61,93]. Nevertheless, some of the countries such as Uganda have taken the actions to rectify those systemic challenges and reported improvement in the implementation [62].…”
Section: Discussionmentioning
confidence: 99%
“…IDSR core functions Improvements in IDSR system attributes such as completeness and timeliness of data reporting after scaling up IDSR have been observed in some SSA countries including Uganda, Malawi and Ghana [37,48,61,63]. Recent statistics indicated that by end of 2017, about two-thirds (68%) of the countries in the WHO Africa Region had achieved the timeliness and completeness threshold of at least 80% of the reporting units [23].…”
Section: Performance Of Idsr Strategymentioning
confidence: 99%
“…[ 7 8 ] Implementation of IDSR has been especially limited in private health facilities, probably as a result of their low involvement in disease control efforts. [ 9 10 11 ] Other factors identified as responsible for the poor implementation of IDSR include low knowledge about IDSR, unavailability of reporting tools, and lack of feedback from local and state governments. [ 5 6 7 9 12 ]…”
Section: Introductionmentioning
confidence: 99%